2001
DOI: 10.1021/ja010249w
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Recognition by CD-Sensitive Dimeric Zinc Porphyrin Host. 1. Chiroptical Protocol for Absolute Configurational Assignments of Monoalcohols and Primary Monoamines

Abstract: A general microscale protocol for the determination of absolute configurations of primary amino groups or secondary hydroxyl groups linked to a single stereogenic center is described. The chiral substrates are linked to the achiral trifunctional bidentate carrier molecule (3-aminopropylamino)acetic acid (1, H(2)NCH(2)CH(2)CH(2)NHCH(2)COOH) and the resultant conjugates are then complexed with dimeric zinc porphyrin host 2 giving rise to 1:1 host/guest sandwiched complexes. These complexes exhibit exciton-couple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
144
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(157 citation statements)
references
References 48 publications
13
144
0
Order By: Relevance
“…The chiral memory on 103 was stable with just a small decrease of the CD intensity over one day. In the case of flexible bound porphyrins, the corresponding bis-porphyrin, 104 (Figure 28), required a bidentate enantiopure ligand to adopt the supramolecular chiral tweezer conformation [76,77]. Hence, the interaction of 104 with various chiral diamines resulted in the induction of a CD couplet in the region of porphyrin absorption.…”
Section: Achiral Porphyrinoids With Achiral Linkagementioning
confidence: 99%
“…The chiral memory on 103 was stable with just a small decrease of the CD intensity over one day. In the case of flexible bound porphyrins, the corresponding bis-porphyrin, 104 (Figure 28), required a bidentate enantiopure ligand to adopt the supramolecular chiral tweezer conformation [76,77]. Hence, the interaction of 104 with various chiral diamines resulted in the induction of a CD couplet in the region of porphyrin absorption.…”
Section: Achiral Porphyrinoids With Achiral Linkagementioning
confidence: 99%
“…The complexation between CD-silent zinc porphyrins and chiral amines or alcohols is another important intermolecular interaction applied to prepare optically active complexes. Berova et al have designed an achiral zinc bis-porphyrin linked with a long pentamethylene diester (host molecule) as shown in Figure 1 [46][47][48]. By relatively intense coordination interactions between zinc porphyrin and nitrogen or oxygen, the host molecules successfully bound plenty of chiral diamines, amino alcohols and amino acids and showed clear ICD effects, due to the formation of CD-active 1:1 and 1:2 host-guest complexes.…”
Section: Induced Circular Dichroism For Oligomersmentioning
confidence: 99%
“…Achiral CD-silent Zn bis-porphyrin linked with a flexible linker gave rise to CD-active 1:1 and 1:2 host-guest complexes with chiral amines and chiral alcohols, arising from relatively intense Zn/N and Zn/O coordination abilities. Berova, Nakanishi and coworkers [102][103][104] designed molecular chromophoric tweezers based on two Zn porphyrins linked with a long floppy pentamethylene diester to bind a number of chiral diamines, amino acid derivatives and amino alcohol derivatives in n-hexane, characterized by CD spectroscopy (Figures 7 and 8). Borovkov and Inoue [105][106][107][108][109] showed that a twisted zinc porphyrin rotamer linked with a shorter ethane spacer can efficiently switch between syn-and anti-forms with P(plus)-and M(minus) sense by step-wise coordination with a family of chiral secondary amines and chiral secondary alcohols, proven by variable temperature UV-Vis and CD spectra and ) of chiral fluid can induce certain chiral geometry in carefully designed non-chiral hosts in double-minimal-well or multi-minimal-well potentials dissolved in fluidic condition at ambient temperature.…”
Section: Optically Active Supramolecules In the Ground Statementioning
confidence: 99%